Champagne and Meatballs: Adventures of a Canadian Communist - Epp, Stefan (Labour / Le Travail, 2012)
The article reviews the book, "Champagne and Meatballs: Adventures of a Canadian Communist," by Bert Whyte, edited by Larry Hannant.
Keywords: BOOKS -- Reviews; CHAMPAGNE & Meatballs: Adventures of a Canadian Communist (Book); Canada; Communism; HANNANT, Larry; Nonfiction; WHYTE, Bert